Bio-optical characteristics along the Straits of Magallanes. (15th May 2016) - Lutz, Vivian; Frouin, Robert; Negri, Rubén; Silva, Ricardo; Pompeu, Mayza; Rudorff, Natalia; Cabral, Anderson; Dogliotti, Ana; Martinez, Gustavo
Abstract: The Straits of Magallanes at the tip of South America connects the Atlantic and Pacific Oceans. The variability in the absorption characteristics by phytoplankton ( aph (440)), non-pigmented particles, NPP ( a NPP (440)), and chromophoric dissolved organic matter, CDOM ( a y (440)), measured along the Straits in late summer 2011 (R/V Melville MV1102 cruise), was analyzed. Satellite-derived monthly PAR data showed that at the time of the cruise the western sector was exposed to a low-light environment ( 16 mol quanta m −2 d −1 ) while the eastern sector received higher irradiance ( 28 mol quanta m −2 d −1 ). In the Patagonian Shelf total absorption was dominated by phytoplankton (up to 76%; aph (440)=0.265 m −1 ), while in the Atlantic Sector of the Straits, the major contributor was NPP (up to 42%; a NPP (440)=0.138 m −1 ), and in the Pacific Sector of the Straits CDOM contributed up to 80% of the total absorption ( a y (440)=0.232 m −1 ). These changes could be related in part to the input of fresh water from glacier melting and rain in the Pacific Sector ( a y (440) vs salinity rs =−0.98). The carbon biomass (C) was composed in its majority by pico-phytoplankton and secondly by nano-phytoplankton, with exception of the Atlantic Sector where the micro-phytoplankton dominated. Carbon to chlorophyll-a ratios (C:Chla) were very low throughout the Straits (average of 6) because of photoacclimation to the extremely low light. Complementary pigments data obtained in spring 2003 by the BEAGLE expedition indicated the predominance of diatoms all along the Straits, but the bio-optical trend resembled the one found in late summer 2011, i.e., NPP dominated the absorption in the well mixed Atlantic Sector, phytoplankton in the Middle Sector, and CDOM in the Pacific Sector. These results emphasize that underwater light is the major factor affecting phytoplankton growth and physiology, and that prevalent physical and geochemical conditions play an important role regulating the bio-optical properties in this heterogeneous area. These effects should be considered to adjust parameters (such as C:Chla) when running biogeochemical models for this region. Highlights: Light controls phytoplankton distribution and physiology in the Straits of Magallanes. Photoacclimation to permanent low light resulted in low C:Chla and Zea:Chla; and high Fuco:Chla. Non-pigmented-particles, phytoplankton, CDOM dominate absorption in that order from the Atlantic to the Pacific. Pico-phytoplankton dominated in late summer and diatoms in spring. These results are relevant for biogeochemical modeling.